Directly observed therapy of sofosbuvir/ribavirin +/− peginterferon with minimal monitoring for the treatment of chronic hepatitis C in people with a history of drug use in Chennai, India (C‐DOT). Issue 1 (14th August 2017) - Solomon, S. S.; Sulkowski, M. S.; Amrose, P.; Srikrishnan, A. K.; McFall, A. M.; Ramasamy, B.; Kumar, M. S.; Anand, S.; Thomas, D. L.; Mehta, S. H.
Summary: We assessed the feasibility of field‐based directly observed therapy (DOT) with minimal monitoring to deliver HCV treatment to people with a history of drug use in Chennai, India. Fifty participants were randomized 1:1 to sofosbuvir+peginterferon alfa 2a+ribavirin (SOF+PR) for 12 weeks (Arm 1) vs sofosbuvir+ribavirin (SOF+R) for 24 weeks (Arm 2). SOF+R was delivered daily at participant chosen venues and weekly peginterferon injections at the study clinic. HCV RNA testing was performed to confirm active HCV infection and sustained virologic response 12 weeks after treatment completion (SVR12). No baseline genotyping or on‐treatment viral loads were performed. Median age was 46 years. All were male and 20% had significant fibrosis/cirrhosis. All self‐reported history of injection drug use, 18% recent noninjection drug use and 38% alcohol dependence. Six discontinued treatment (88% completed treatment in each arm). Of 22 who completed SOF+PR, all achieved SVR12 (22/25=88%); 15 of 22 who completed SOF+R achieved SVR12 (15/25=60%; P =.05). Among those completing SOF+R, SVR12 was significantly less common in participants reporting ongoing substance use (36% vs 100%) and missed doses. Active substance use and missed doses did not impact SVR with SOF+PR. Field‐based DOT of HCV therapy without real‐time HCV RNA monitoring was feasible; however, achieving 100% adherence was challenging. SOF+PR appeared superior to SOF+R in achieving SVR12, even when doses were missed with no discontinuations due to side effects. Further exploration of short duration treatment with peginterferon plus direct‐acting antivirals is warranted.